Bacillus subtilis as a growth promoter of forest species seedlings - Chagas Junior, Aloisio Freitas; Martins, Albert Lennon Lima; Chagas, Lillian França Borges; Giongo, Marcos; da Silva, Damiana Beatriz; de Sousa, Kellen Angela O.; Rocha, Adilon Martins; Moura, Dallila Moreira de Oliveira; de Almeida, Leticia Bezerra; de Souza, Bruna Marques (Seven Editora, 2023)
Native forest species have been employed for several purposes, such as the recovery of degraded areas, reforestation, and afforestation. The growth-promoting microorganisms are a viable alternative to producing native forest seedlings. The Bacillus subtilis is an alternative since it stands out by promoting plant growth through the solubilization of phosphate, production of phytohormones, and the availability of nutrients. The present work aimed to evaluate the influence of Bacillus subtilis in the initial growth of fava-tamboril (Enterolobium maximum), amarelão (Apuleia leiocarpa), and paricá (Schizolobium amazonicum) seedlings. Inoculations were made with two strains of Bacillus subtilis (Bs08, Bs10) and the commercial product based on Bacillus subtilis PANTA©, using 1 mL of the solution of each strain, and a control sample with water only, using a graduated pipette. An entirely randomized design with three treatments and eight repetitions was used. The variables analysed were plant height (PH), stem diameter (SD), root volume (RV), root dry weight (RDW), above-ground biomass weight (AGB), and Dickson quality index (DQI). In general, inoculation with Bacillus subtilis, with both strains evaluated and the commercial inoculant (PANTA ©), provided gains in biomass and in the DQI of plants at 30 and 60 days after emergence. Thus, the inoculation of Bacillus subtilis showed promising results as a growth promoter for paricá, fava-tamboril, and amarelão. DOi:https://doi.org/10.56238/uniknowindevolp-122